2009
DOI: 10.1111/j.1474-919x.2008.00904.x
|View full text |Cite
|
Sign up to set email alerts
|

Diet and food preferences of the endangered Bearded Vulture Gypaetus barbatus: a basis for their conservation

Abstract: The Bearded Vulture Gypaetus barbatus population in the Pyrenees is managed using feeding stations to increase breeding success and reduce mortality in the pre‐adult population. Nevertheless, very little quantitative and qualitative information has been published on such basic aspects of the species’ ecology as feeding habits and dietary preferences. This study investigated both aspects through direct and unbiased observation of breeding Bearded Vultures during the chick‐rearing period. Bearded Vulture diet co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 41 publications
3
82
1
Order By: Relevance
“…Consequently, it can be predicted that the growth of Iberian griffon vulture populations could end in the shortterm and even begin to decline in the long-term. Breeding counts carried out in northern Spain during 2007 and 2008 indicate this trend (Margalida et al 2009). …”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Consequently, it can be predicted that the growth of Iberian griffon vulture populations could end in the shortterm and even begin to decline in the long-term. Breeding counts carried out in northern Spain during 2007 and 2008 indicate this trend (Margalida et al 2009). …”
Section: Discussionmentioning
confidence: 91%
“…The scarcity of the main food resources exploited by the griffon vultures (predictable large carcasses) would lead to an increase in indirect competition with subordinate species for small and medium-sized carcasses, in a process similar to the hyperpredation observed in predator-prey systems (Courchamp et al 2000). In the Iberian Peninsula the carcasses of wild rabbits are heavily exploited by facultative predators and carrion-eaters (Delibes-Mateos et al 2008) and for some threatened species like the Egyptian vulture, the cinereous vulture (Aegypius monachus) and the bearded vulture (Gypaetus barbatus) constitute an essential part of the diet during the breeding period (Hiraldo 1976;Donázar and Ceballos 1988;Margalida et al 2009). In a field experiment carried out during 2005 and 2006, when the availability of large carcasses was still high, we observed that 30% of the wild rabbit carcasses were consumed by griffon vultures, which displaced other species like Egyptian vultures, red kites (Milvus milvus), black kites (Milvus migrans), marh harriers (Circus aeruginosus), common European buzzards (Buteo buteo), and common ravens (Corvus corax).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…vultures to protect the remaining populations on the Indian subcontinent, it is equally important to recognize risks to worldwide populations of various species of vultures and other avian scavengers. The latter group of birds is probably equally at risk of accidental toxicity as many countries (Namibia, Spain, India, Italy, Israel) have introduced ''vulture restaurants,'' where colonies are artificially fed through routine placement of carcasses (Meretsky and Mannan 1999;Bamford et al, 2007;Gilbert et al, 2007;Cortes-Avizanda et al, 2009;Gustin et al, 2009;Margalida et al, 2009). Hence, if any other NSAIDs (e.g., carprofen, flunixin meglumine, phenylbutazone, tolfenamic acid, meclofenamic acid, and ibuprofen) were to prove as toxic as diclofenac and ketoprofen, these vulture populations might also be at risk.…”
Section: Introductionmentioning
confidence: 99%